2001
DOI: 10.1073/pnas.091056898
|View full text |Cite
|
Sign up to set email alerts
|

Global survey of genetic variation in CCR5 , RANTES , and MIP-1 α: Impact on the epidemiology of the HIV-1 pandemic

Abstract: Expression of CC chemokine receptor 5 (CCR5), the major coreceptor for HIV-1 cell entry, and its ligands (e.g., RANTES and MIP-1␣) is widely regarded as central to the pathogenesis of HIV-1 infection. By surveying nearly 3,000 HIV؉ and HIV؊ individuals from worldwide populations for polymorphisms in the genes encoding RANTES, MIP-1␣, and CCR5, we show that the evolutionary histories of human populations have had a significant impact on the distribution of variation in these genes, and that this may be responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
190
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 211 publications
(208 citation statements)
references
References 30 publications
13
190
4
Order By: Relevance
“…The -403A-28G haplotype was shown to be associated with delayed disease progression in HIV-1 infected Japanese, but exerts no influence on the incidence of HIV-1 infection [52]. In European-Americans, the compound genotype -403G/A -28C/C was reported to be resistant to AIDS progression in one study [53], but not in another [54]. These RANTES polymorphisms have no effect on HIV-1 infection and disease progression in African-Americans [54].…”
Section: Variation In Rantesmentioning
confidence: 97%
See 4 more Smart Citations
“…The -403A-28G haplotype was shown to be associated with delayed disease progression in HIV-1 infected Japanese, but exerts no influence on the incidence of HIV-1 infection [52]. In European-Americans, the compound genotype -403G/A -28C/C was reported to be resistant to AIDS progression in one study [53], but not in another [54]. These RANTES polymorphisms have no effect on HIV-1 infection and disease progression in African-Americans [54].…”
Section: Variation In Rantesmentioning
confidence: 97%
“…In European-Americans, the compound genotype -403G/A -28C/C was reported to be resistant to AIDS progression in one study [53], but not in another [54]. These RANTES polymorphisms have no effect on HIV-1 infection and disease progression in African-Americans [54]. Most recently, An et al have found that 3 SNPs (-403A in the promoter, In1.1C in the first intron, and 3'222C in the 3' untranslated region) are associated with increased frequency of HIV-1 infection, and that the In1.1C allele or haplotypes display a strong association with rapid progression to AIDS among HIV-1 infected African-Americans and European-Americans [108].…”
Section: Variation In Rantesmentioning
confidence: 97%
See 3 more Smart Citations